Four-layer co-extrusion infusion film and preparation method thereof

Through the four-layer co-extrusion membrane structure for infusion, combined with nano zinc oxide and aminoacrylate and other materials, the problems of large permeability and insufficient antibacterial properties in the prior art are solved, and higher water vapor barrier and antibacterial properties are achieved. Ensure the stability and safety of the drug.

CN119159885AActive Publication Date: 2024-12-20CHONGZHOU JUNJIAN PLASTIC CO LTD

Patent Information

Application Number
CN202411315201.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-20
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing multi-layer co-extruded infusion membranes have problems such as large permeability of water vapor and insufficient antibacterial properties, which affects the stability of the drug and the safety of the drug.

Method used

Four-layer coextrusion infusion membrane structure, in which the outer layer contains nano zinc oxide and aminoacrylate, the secondary outer layer is homopolymer polypropylene and elastomer, the middle layer is copolymer polypropylene and cycloolefin copolymer, and the inner layer is binary Copolymerized polypropylene and chitosan are coated with nano zinc oxide through coextrusion blown film process and ultrasonic vibrating screen, combined with irradiation treatment, to improve the water vapor barrier and antibacterial properties of the film.

Benefits of technology

It significantly improves the water vapor barrier ability and antibacterial properties, ensures the stability of the drug and the safety of drug use, and has a simple production process and good biocompatibility of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159885A_ABST
    Figure CN119159885A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of infusion bag films, and provides a four-layer co-extrusion infusion film which comprises an outer layer, a secondary outer layer, a middle layer and an inner layer, and the outer layer comprises the following raw material components in parts by weight: 20-35 parts of nano zinc oxide and 50-80 parts of amino acrylate; the secondary outer layer is prepared from the following raw material components in parts by weight: 70 to 90 parts of homo-polypropylene and 10 to 30 parts of elastomer; the middle layer is prepared from the following raw material components in parts by weight: 20 to 40 parts of co-polypropylene, 40 to 60 parts of elastomer and 10 to 20 parts of cycloolefin copolymer; the inner layer is prepared from the following raw material components in parts by weight: 60 to 80 parts of binary co-polypropylene, 20 to 40 parts of elastomer and 1 to 3 parts of chitosan; according to the invention, the bonding strength between the nano zinc oxide and the outer film surface can be fully improved, the adhesive force is strong, and the antibacterial effect can be maintained for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of films for infusion bags, and in particular, relates to a four-layer co-extruded infusion film and a preparation method thereof. Background Art

[0002] Although traditional glass infusion bottles have the advantages of low cost and good compatibility with drugs, they have disadvantages such as large mass, large volume, difficult transportation, and easy to break. Plastic bottles have solved the problems of glass bottles to a certain extent, but during use, they need to add internal pressure to make the liquid drip out, increasing the risk of secondary pollution. Then, PVC soft bags came into being, but PVC materials contain polyvinyl chloride monomers, which are not good for human health. At the same time, the plasticizer diethyl phthalate (DEHP) in PVC materials is easy to precipitate and enter the human body with the drug solution, causing damage to the human body.

[0003] Therefore, in the prior art, non-PVC soft bags are used to solve the problems existing in the above-mentioned PVC soft bags, such as the patent with announcement number CN202716491U, which discloses a new type of three-layer co-extruded infusion bag film. Specifically, it discloses an infusion bag film made of polypropylene or modified polypropylene, which is made by a three-layer co-extrusion process, has high transparency, does not turn white during disinfection and use, and has good sterilization adaptability;

[0004] However, although the non-PVC soft bags in the prior art have good mechanical properties and stable physical and chemical properties, and solve the technical problem of the need to use plasticizers in PVC materials, they still have the defects of high water vapor permeability and insufficient antibacterial performance, just like other multi-layer co-extruded infusion films currently used in China, and thus still cannot guarantee the stability of most drugs and the safety of medication.

[0005] Therefore, based on the above description, there is an urgent need for a multi-layer co-extruded infusion film with strong water vapor barrier capability and good antibacterial properties. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the first object of the present invention is to provide a four-layer co-extruded infusion film with strong water vapor barrier ability and good antibacterial properties to ensure safety and stability during medication.

[0007] The present invention is achieved through the following technical solutions:

[0008] A three-layer co-extruded infusion film, comprising an outer layer, a sub-outer layer, a middle layer and an inner layer.

[0009] The outer layer comprises the following raw material components and weight proportions: 20-35 parts of nano zinc oxide and 50-80 parts of amino acrylate;

[0010] The secondary outer layer comprises the following raw material components and weight proportions: 70-90 parts of homopolypropylene and 10-30 parts of elastomer;

[0011] The middle layer comprises the following raw material components and weight proportions: 20-40 parts of copolymerized polypropylene, 40-60 parts of elastomer, and 10-20 parts of cycloolefin copolymer;

[0012] The inner layer comprises the following raw material components and their weight proportions: 60-80 parts of binary copolymer polypropylene, 20-40 parts of elastomer, and 1-3 parts of chitosan.

[0013] Among them, binary copolymer polypropylene can also be replaced by ternary copolymer polypropylene;

[0014] Among them, in the outermost layer formula, amino acrylate can provide amino active groups to graft nano zinc oxide. At the same time, the acrylate group can provide a certain viscosity, which can quickly bond the nano zinc oxide to the surface of the outer film, fully improving the stability of the nano oxidative properties.

[0015] Among them, in the middle layer formula, the added cyclic olefin copolymer has excellent properties such as high strength, high transparency, water vapor barrier, and chemical inertness. However, when used as a packaging material, the hardness is too large to be formed alone; furthermore, blending cyclic olefin copolymer with polypropylene and elastomer can not only solve the molding problem when using pure cyclic olefin copolymer, but also improve the thermal stability, water vapor barrier and other properties of the blended material without adding a barrier layer.

[0016] Among them, a natural and harmless biological antibacterial agent - chitosan is added to the inner layer formula system. Chitosan has good biocompatibility and biological activity, and will not cause harm to the efficacy of the drug or the human body. By blending chitosan, polypropylene and elastomer, not only the production process is simple, but also the inner layer material can be given certain antibacterial properties, ensuring the safety and stability of infusion drugs during use.

[0017] Furthermore, the elastomer is at least one of styrene-ethylene-butylene-styrene block copolymer, styrene-ethylene-propylene-styrene copolymer, and polyolefin elastomer.

[0018] Furthermore, the outer layer has a thickness of 1-10 μm.

[0019] Furthermore, the secondary outer layer has a thickness of 20-30 μm.

[0020] Furthermore, the middle layer has a thickness of 120-160 μm.

[0021] Furthermore, the inner layer has a thickness of 20-40 μm.

[0022] Furthermore, the total thickness of the infusion membrane is 190-220 μm.

[0023] The second object of the present invention is to provide a method for preparing the above-mentioned four-layer co-extruded infusion film, comprising the following steps:

[0024] S1 adopts a three-layer co-extrusion bottom-blowing water-cooled film blowing process. The outer layer raw material, the middle layer raw material and the inner layer raw material are mixed evenly according to the corresponding mass ratio, put into a co-extrusion film blowing machine for co-extrusion film blowing, and then sequentially cooled by a water ring and rolled into a tube film to obtain a composite film;

[0025] S2 uses amino acrylate to spray the outer surface of the composite film, and then evenly sieves and sprinkles nano zinc oxide on the surface of the amino acrylate coating under ultrasonic vibration to obtain a prefabricated film;

[0026] S3: placing the prefabricated film in an oxygen atmosphere, irradiating it, standing it for 1-5 minutes, and then drying it to obtain a film for infusion.

[0027] Among them, amino acrylate contains amino and acrylate groups in its molecules, so it has the active groups of amino and the adhesive properties of acrylate. Furthermore, after spraying, it can quickly adhere to the surface of the outer film, and then nano zinc oxide is sieved on the surface of the amino acrylate coating by ultrasonic vibration. The amino acrylate can quickly bond with the nano zinc oxide particles, and with the vibration, the nano zinc oxide particles are uniformly embedded or immersed in the interior of the amino acrylate; further, by irradiation treatment in an oxygen atmosphere, after the rays pass through the amino acrylate, the nano zinc oxide layer and the outer film material, active groups such as hydroxyl, carboxyl, amide, etc. are generated on the surface of the outer film material to react with the amino active groups in the amino acrylate, so that the nano zinc oxide is firmly grafted to the surface of the outer film.

[0028] Furthermore, in step S1, the extrusion temperature of the sub-outer layer is 190-210°C, the extrusion temperature of the middle layer is 180-210°C, and the extrusion temperature of the inner layer is 190-200°C.

[0029] Furthermore, in step S2, the ultrasonic frequency range is 30-40 KHz, and the pore size of the vibrating screen is 20-30 nm.

[0030] Furthermore, in step S3, the radiation source is cobalt-60 gamma rays, the irradiation dose is 2-10 Gy, and the irradiation dose rate is 10 Gy / min.

[0031] The beneficial effects of the present invention are:

[0032] (1) By adding amino acrylate to the outer layer formula, it can provide amino active groups to graft nano zinc oxide. At the same time, the acrylate group can provide a certain viscosity, thereby making the nano zinc oxide have a high bonding strength and strong adhesion to the outer layer film surface, and can maintain the antibacterial effect for a long time.

[0033] (2) Blending cycloolefin copolymer with polypropylene and elastomer can not only solve the molding problem when using pure cycloolefin copolymer, but also improve the water vapor barrier properties of the blended material without adding a barrier layer.

[0034] (3) By blending chitosan, polypropylene and elastomer, not only is the production process simple, but the inner layer material can also be given certain antibacterial properties, ensuring the safety and stability of infusion drugs during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 It is a schematic diagram of the cross-sectional structure of part of the membrane layer according to an embodiment of the present invention.

[0037] Icon: 1-outer layer, 2-second outer layer, 3-middle layer, 4-inner layer. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0039] Example

[0040] Example 1

[0041] This embodiment provides a four-layer co-extruded infusion film, (1) the outer layer raw materials and components thereof, by weight, are 20 parts of nano zinc oxide and 80 parts of amino acrylate, with a thickness of 5 μm; (2) the secondary outer layer raw materials and components thereof, by weight, are 90 parts of homopolypropylene and 10 parts of styrene-ethylene-butylene-styrene block copolymer. 份, thickness is 25μm; (3) the middle layer raw materials and components used are, by weight, 30 parts of copolymerized polypropylene, 60 parts of styrene-ethylene-butylene-styrene block copolymer, and 10 parts of cycloolefin copolymer, with a thickness of 145μm; (4) the inner layer raw materials and components used are, by weight, 60 parts of binary polypropylene, 37 parts of styrene-ethylene-butylene-styrene block copolymer, and 3 parts of chitosan, with a thickness of 20μm; (5) according to the above formula, the pellets are mixed evenly, and a three-layer co-extrusion film blowing machine is used to ensure that the die head temperature is 180-210℃, melt extrusion, blown into film, and then The film was cooled by a water ring and rolled into a tube to obtain a composite film; further, 65 parts of amino acrylate were sprayed on the outer surface of the composite film by weight using a high-pressure airless spray method, and then 20 parts of nano zinc oxide dry powder were evenly sieved and sprinkled on the surface of the amino acrylate coating at a frequency of 35KHz using an ultrasonic vibration screen with an aperture of 25nm to obtain a prefabricated film; the prefabricated film was placed in an oxygen atmosphere for irradiation treatment, the radiation source was cobalt-60 gamma rays, the irradiation dose was 2Gy, the irradiation dose rate was 10Gy / min, and after standing for 1 minute, it was dried by air blast to obtain a film for infusion.

[0042] Example 2

[0043] This embodiment provides a four-layer co-extruded infusion film, (1) the outer layer raw materials and components thereof, by weight, are 23 parts of nano zinc oxide and 77 parts of amino acrylate, with a thickness of 5 μm; (2) the secondary outer layer raw materials and components thereof, by weight, are 90 parts of homopolypropylene and 10 parts of styrene-ethylene-butylene-styrene block copolymer. 份, thickness is 25μm; (3) the raw materials and components of the middle layer used are, by weight, 30 parts of copolymerized polypropylene, 60 parts of styrene-ethylene-butylene-styrene block copolymer, and 10 parts of cycloolefin copolymer, with a thickness of 150μm; (4) the raw materials and components of the inner layer used are, by weight, 60 parts of binary polypropylene, 37 parts of styrene-ethylene-butylene-styrene block copolymer, and 3 parts of chitosan, with a thickness of 20μm; (5) according to the above formula, the pellets are mixed evenly, and a three-layer co-extrusion film blowing machine is used to ensure that the die head temperature is 180-210℃, melt extrusion, blown into film, and then The film was cooled by a water ring and rolled into a tube to obtain a composite film; further, 65 parts of amino acrylate were sprayed on the outer surface of the composite film by high-pressure airless spraying, and then 23 parts of nano zinc oxide dry powder were evenly sieved on the surface of the amino acrylate coating at a frequency of 35KHz using an ultrasonic vibration screen with an aperture of 25nm to obtain a prefabricated film; the prefabricated film was placed in an oxygen atmosphere for irradiation treatment, the radiation source was cobalt-60 gamma rays, the irradiation dose was 2Gy, the irradiation dose rate was 10Gy / min, and after standing for 1 minute, it was dried by air blast to obtain a film for infusion.

[0044] Example 3

[0045] This embodiment provides a four-layer co-extruded infusion film, (1) the outer layer raw materials and components thereof, by weight, are 26 parts of nano zinc oxide and 74 parts of amino acrylate, with a thickness of 5 μm; (2) the secondary outer layer raw materials and components thereof, by weight, are 90 parts of homopolypropylene and 10 parts of styrene-ethylene-butylene-styrene block copolymer. 份, thickness is 25μm; (3) the raw materials and components of the middle layer used are, by weight, 30 parts of copolymerized polypropylene, 60 parts of styrene-ethylene-butylene-styrene block copolymer, and 10 parts of cycloolefin copolymer, with a thickness of 150μm; (4) the raw materials and components of the inner layer used are, by weight, 60 parts of binary polypropylene, 37 parts of styrene-ethylene-butylene-styrene block copolymer, and 3 parts of chitosan, with a thickness of 25μm; (5) according to the above formula, the pellets are mixed evenly, and a three-layer co-extrusion film blowing machine is used to ensure that the die head temperature is 180-210℃, melt extrusion, blown into film, and then The film was cooled by a water ring and rolled into a tube to obtain a composite film; further, 65 parts of amino acrylate were sprayed on the outer surface of the composite film by high-pressure airless spraying, and then 26 parts of nano zinc oxide dry powder were evenly sieved on the surface of the amino acrylate coating at a frequency of 35KHz using an ultrasonic vibration screen with an aperture of 25nm to obtain a prefabricated film; the prefabricated film was placed in an oxygen atmosphere for irradiation treatment, the radiation source was cobalt-60 gamma rays, the irradiation dose was 2Gy, the irradiation dose rate was 10Gy / min, and after standing for 1 minute, it was dried by air blast to obtain a film for infusion.

[0046] Example 4

[0047] This embodiment provides a four-layer co-extruded infusion film, (1) the outer layer raw materials and components thereof, by weight, are 29 parts of nano zinc oxide and 71 parts of amino acrylate, with a thickness of 5 μm; (2) the secondary outer layer raw materials and components thereof, by weight, are 90 parts of homopolypropylene and 10 parts of styrene-ethylene-butylene-styrene block copolymer. 份, thickness is 25μm; (3) the raw materials and components of the middle layer used are, by weight, 30 parts of copolymerized polypropylene, 60 parts of styrene-ethylene-butylene-styrene block copolymer, and 10 parts of cycloolefin copolymer, with a thickness of 155μm; (4) the raw materials and components of the inner layer used are, by weight, 60 parts of binary polypropylene, 37 parts of styrene-ethylene-butylene-styrene block copolymer, and 3 parts of chitosan, with a thickness of 25μm; (5) according to the above formula, the pellets are mixed evenly, and a three-layer co-extrusion film blowing machine is used to ensure that the die head temperature is 180-210℃, melt extrusion, blown into film, and then The film was cooled by a water ring and rolled into a tube to obtain a composite film; further, 65 parts of amino acrylate were sprayed on the outer surface of the composite film by high-pressure airless spraying, and then 29 parts of nano zinc oxide dry powder were evenly sieved on the surface of the amino acrylate coating at a frequency of 35KHz using an ultrasonic vibration screen with an aperture of 25nm to obtain a prefabricated film; the prefabricated film was placed in an oxygen atmosphere for irradiation treatment, the radiation source was cobalt-60 gamma rays, the irradiation dose was 2Gy, the irradiation dose rate was 10Gy / min, and after standing for 1 minute, it was dried by air blast to obtain a film for infusion.

[0048] Example 5

[0049] This embodiment provides a four-layer co-extruded infusion film, (1) the outer layer raw materials and components thereof, by weight, are 32 parts of nano zinc oxide and 68 parts of amino acrylate, with a thickness of 5 μm; (2) the secondary outer layer raw materials and components thereof, by weight, are 90 parts of homopolypropylene and 10 parts of styrene-ethylene-butylene-styrene block copolymer. 份, thickness is 25μm; (3) the raw materials and components of the middle layer used are, by weight, 30 parts of copolymerized polypropylene, 60 parts of styrene-ethylene-butylene-styrene block copolymer, and 10 parts of cycloolefin copolymer, with a thickness of 155μm; (4) the raw materials and components of the inner layer used are, by weight, 60 parts of binary polypropylene, 37 parts of styrene-ethylene-butylene-styrene block copolymer, and 3 parts of chitosan, with a thickness of 30μm; (5) according to the above formula, the pellets are mixed evenly, and a three-layer co-extrusion film blowing machine is used to ensure that the die head temperature is 180-210℃, melt extrusion, blown into film, and then The film was cooled by a water ring and rolled into a tube to obtain a composite film; further, 65 parts of amino acrylate were sprayed on the outer surface of the composite film by high-pressure airless spraying, and then 32 parts of nano zinc oxide dry powder were evenly sieved on the surface of the amino acrylate coating at a frequency of 35KHz using an ultrasonic vibration screen with an aperture of 25nm to obtain a prefabricated film; the prefabricated film was placed in an oxygen atmosphere for irradiation treatment, the radiation source was cobalt-60 gamma rays, the irradiation dose was 2Gy, the irradiation dose rate was 10Gy / min, and after standing for 1 minute, it was dried by air blast to obtain a film for infusion.

[0050] Example 6

[0051] This embodiment provides a four-layer co-extruded infusion film, (1) the outer layer raw materials and components thereof, by weight, are 32 parts of nano zinc oxide and 68 parts of amino acrylate, with a thickness of 5 μm; (2) the secondary outer layer raw materials and components thereof, by weight, are 90 parts of homopolypropylene and 10 parts of styrene-ethylene-butylene-styrene block copolymer. 份, thickness is 25μm; (3) the middle layer raw materials and components used are, by weight, 30 parts of copolymerized polypropylene, 60 parts of styrene-ethylene-butylene-styrene block copolymer, and 10 parts of cycloolefin copolymer, with a thickness of 160μm; (4) the inner layer raw materials and components used are, by weight, 60 parts of binary polypropylene, 37 parts of styrene-ethylene-butylene-styrene block copolymer, and 3 parts of chitosan, with a thickness of 30μm; (5) according to the above formula, the pellets are mixed evenly, and a three-layer co-extrusion film blowing machine is used to ensure that the die head temperature is 180-210℃, melt extrusion, blown into film, and then The film was cooled by a water ring and rolled into a tube to obtain a composite film; further, 65 parts of amino acrylate were sprayed on the outer surface of the composite film by high-pressure airless spraying, and then 32 parts of nano zinc oxide dry powder were evenly sieved on the surface of the amino acrylate coating at a frequency of 35KHz using an ultrasonic vibration screen with an aperture of 25nm to obtain a prefabricated film; the prefabricated film was placed in an oxygen atmosphere for irradiation treatment, the radiation source was cobalt-60 gamma rays, the irradiation dose was 2Gy, the irradiation dose rate was 10Gy / min, and after standing for 1 minute, it was dried by air blast to obtain a film for infusion.

[0052] Comparative Example

[0053] Comparative Example 1

[0054] The difference between this comparative example and Example 1 is that no outer layer is used, and the nano zinc oxide aqueous solution is directly applied to the sub-outer layer.

[0055] Comparative Example 2

[0056] The difference between this comparative example and Example 1 is that a nano zinc oxide aqueous solution is applied to the surface of the amino acrylate.

[0057] Comparative Example 3

[0058] The difference between this comparative example and Example 1 is that the outer layer raw materials and components used therein are, by weight, 10 parts of nano zinc oxide and 90 parts of amino acrylate.

[0059] Comparative Example 4

[0060] The difference between this comparative example and Example 1 is that the outer layer raw materials and components used therein are, by weight, 60 parts of nano zinc oxide and 40 parts of amino acrylate.

[0061] Comparative Example 5

[0062] The difference between this comparative example and Example 1 is that the middle layer raw materials and components used therein are, by weight, 40 parts of copolymerized polypropylene and 60 parts of styrene-ethylene-butylene-styrene block copolymer, and the thickness is 145 μm.

[0063] Comparative Example 6

[0064] The difference between this comparative example and Example 1 is that the inner layer raw materials and components used therein are, by weight, 60 parts of binary polypropylene and 40 parts of styrene-ethylene-butylene-styrene block copolymer, and the thickness is 20 μm.

[0065] Test example

[0066] The membranes produced in Examples 1-6 and Comparative Examples 1-6 were tested for tensile strength, water vapor permeability, and antibacterial rate. The test results are shown in Table 1:

[0067] Table 1

[0068]

[0069] According to Table 1, by comparing and analyzing Examples 1-6 with Comparative Examples 1-6, it can be seen that by adding an appropriate weight portion of aminoacrylate in the outer layer formula, the stability of the outer nano zinc oxide and the uniformity of the coverage can be improved, thereby greatly improving the antibacterial effect; in addition, the use of an ultrasonic vibration screen sifting method, compared with the prior art method of directly brushing the nano zinc oxide aqueous solution, the uniformity and density of the outer layer of nano zinc oxide are better, and the use of cycloolefin copolymer can effectively reduce the water vapor permeability of the middle layer, and chitosan can improve the antibacterial performance of the inner layer.

[0070] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A four-layer co-extruded infusion film, characterized in that: Including outer layer, sub-outer layer, middle layer and inner layer, The outer layer comprises the following raw material components and weight proportions: 25-35 parts of nano zinc oxide and 50-80 parts of amino acrylate; The secondary outer layer comprises the following raw material components and weight proportions: 70-90 parts of homopolypropylene and 10-30 parts of elastomer; The middle layer comprises the following raw material components and weight proportions: 20-40 parts of copolymerized polypropylene, 40-60 parts of elastomer, and 10-20 parts of cycloolefin copolymer; The inner layer comprises the following raw material components and their weight proportions: 60-80 parts of binary copolymer polypropylene, 20-40 parts of elastomer, and 1-3 parts of chitosan.

2. The four-layer co-extruded infusion film according to claim 1, characterized in that: The elastomer is at least one of styrene-ethylene-butylene-styrene block copolymer, styrene-ethylene-propylene-styrene copolymer and polyolefin elastomer.

3. The four-layer co-extruded infusion film according to claim 1, characterized in that: The outer layer has a thickness of 1-10 μm.

4. The four-layer co-extruded infusion film according to claim 1, characterized in that: The thickness of the secondary outer layer is 20-30 μm.

5. The four-layer co-extruded infusion film according to claim 1, characterized in that: The thickness of the middle layer is 120-160 μm.

6. The four-layer co-extruded infusion film according to claim 1, characterized in that: The thickness of the inner layer is 20-40 μm; the total thickness of the infusion membrane is 190-220 μm.

7. The method for preparing a four-layer co-extruded infusion film according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1 adopts a three-layer co-extrusion bottom-blowing water-cooled film blowing process. The outer layer raw material, the middle layer raw material and the inner layer raw material are mixed evenly according to the corresponding mass ratio, put into a co-extrusion film blowing machine for co-extrusion film blowing, and then sequentially cooled by a water ring and rolled into a tube film to obtain a composite film; S2 uses amino acrylate to spray the outer surface of the composite film, and then evenly sieves and sprinkles nano zinc oxide on the surface of the amino acrylate coating under ultrasonic vibration to obtain a prefabricated film; S3: placing the prefabricated film in an oxygen atmosphere, irradiating it, standing it for 1-5 minutes, and then drying it to obtain a film for infusion.

8. The method for preparing a four-layer co-extruded infusion film according to claim 7, characterized in that: In step S1, the extrusion temperature of the outer layer is 190-210°C, the extrusion temperature of the middle layer is 180-210°C, and the extrusion temperature of the inner layer is 190-200°C.

9. The method for preparing a four-layer co-extruded infusion film according to claim 7, characterized in that: In step S2, the ultrasonic frequency range is 30-40 KHz, and the pore size of the vibrating screen is 20-30 nm.

10. The method for preparing a four-layer co-extruded infusion film according to claim 7, characterized in that: In step S3, the radiation source is cobalt-60 gamma rays, the irradiation dose is 2-10 Gy, and the irradiation dose rate is 10 Gy / min.

Citation Information

Patent Citations

  • Novel three-layer co-extrusion film for infusion bag

    CN202716491U

  • Film material for transfusion

    CN111452471A

  • Nano zinc oxide antibacterial coating

    CN112608655A

  • Three-layer co-extrusion polyolefin infusion film and preparation method thereof

    CN113954469A

  • Antibacterial and anticorrosive powder coating preparation equipment and process thereof

    CN116713057A

Cited By

  • Laminated film material for soft infusion bag and preparation method of laminated film material

    CN119773331A

  • A laminated film material for a transfusion soft bag and a method for manufacturing the same

    CN119773331B